Prestasi Belajar AntaraSiswa Program Khusus Dan Reguler(Studi Komparasi Di Mts Negeri 1 Surakarta Tahun 2016) - Panji, Abdul Khaliq Dwi; , Drs. Abdullah Mahmud, M,Ag (2017)
The learning achievement is the result indicated the by students after the teaching and learning process. The learning achievement is usually indicated with a numeric value as a statement of learning outcomes of students to their parents. A good achievement is not an eazy effort because the learning achievement can be affected by various factors, both internal and external ones. In formal education, the school is an educational institution that is critical to the success of student learning, and therefore the school establishes several programs to meet the needs of learners and parents, in order to achieve their objectives. However, the presence of several programs at the school are very influential on the result differences in learning achievement of learners. Based on this background, the purpose of this study is to find out: The differences of learning achievement between students who take specific program classes and the students who attend regular program classes, as well as to find out the similarities between the two groups of the students. This study has focused on the class VIII.1 of specific program and the class VIII.A of reguler program, becouse both are the exellent classes from each program. This research has been conducted at MTs Negeri 1 Surakarta and included in the field research. The subject of this study have been taken from class VIII.1 of specific program and the class VIII.A of reguler program. In data collection this research has applied interview, observation and documentation. In analyzing the data, the author used a qualitative descriptive method. The steps are data reduction, data presentation with charts and text, then drawing conclusions The research result show that there is a difference in learning achievement between students who take special program class and those who take regular program class. The mean of the group who take special program class is 3,44. Meanwhile, the mean of the learning achievement of the group who take reguler program class is 3,32. Such differences in learning achievement are due to several factors including: environmental factors, intelligence, motivation, time, facilities and infrastructure, classroom atmosphere, as well as learning interest of the students. Not much different treatments between the two groups except: giving additional learning, time and content, managing small group membership, and giving air-conditioning facilities to the special program class. Meanwhile, the similarities of treatments between these two group's are applying the same curriculum, 2013 curriculum and the same methods of teacher's teaching, and using the same facilities and infrastructure, including the projector facilities in the classroom.